Abnormal Brain Glucose Metabolism in Papillary Thyroid Cancer Patients 4 Weeks After Withdrawal of Levothyroxine: A Cross-Sectional Study Using 18F-FDG PET/CT - Wu, Shu-qi; Feng, Fang; Zou, Ren-jian; Fu, Hong-liang; Sun, Jia-wei; Jia, Xi-ze; Yin, Ya-fu; Wang, Hui (Frontiers in Endocrinology, 2021)
Background There is no doubt that thyroid dysfunction is associated with psychiatric disorders. A large amount of thyroid carcinoma patients displayed mood disorders after the withdrawal of levothyroxine (LT4). However, it is unclear whether the disorders are related to the transient withdrawal of LT4, and if yes, what the possible underlying mechanism is. This study aims to investigate the abnormal regional cerebral glucose metabolism (rCMRglu) in a group of papillary thyroid cancer (PTC) patients without LT4 for 4 weeks and prove the relationship between the abnormal rCMRglu with depression and anxiety. Methods Brain 18F-FDG PET/CT data of 38 consecutive PTC patients with high/intermediate-risk from June 2016 to December 2017 have been analyzed. Of the 38 patients, 23 are in the LT4 withdrawal group (WG) and 15 in the LT4 replacement group (RG). These patients were also evaluated for depressive and anxiety symptoms within 24 h after the scans based on the Hamilton Depression Rating Scale (17 items, HRDS-17) and the Hamilton Anxiety Rating Scale (HAMA) respectively. Results Thirty-eight patients (12 men, 26 women; age range, 25–69 years; mean age, 45.8 years) were selected in the study. Compared with the RG, patients in WG showed depression and anxiety with higher total scores of HRDS-17 and HAMA (14.7 ± 5.8 vs 3.8 ± 5.5, t = −5.74, p = 0.00; 9.3 ± 4.3 vs 2.7 ± 4.1, t = −4.74, p = 0.00, respectively). In the brain glucose metabolism analysis, the WG patients showed lower rCMRglu in Occipital_Mid_R and Postcentral_L. On the other hand, data illustrated significant rCMRglu increases in the Frontal_Sup_Orb_L. Compared with the healthy group (HG), the rCMRglu of the Postcentral_L and Precuneus_L showed hypoactivity, but the Hippocampus_R and the Temporal_Inf_L showed hyperactivity. This analysis yielded a significant correlation between abnormal rCMRglu with the free thyroxine level, the serum thyroid-stimulating hormone level, HRDS-17, and HAMA scores. Conclusions The findings showed that more PTC patients exhibited depression and anxiety after LT4 withdrawal for 4 weeks. More attention should be paid to these hypothyroid patients while they were in the hospital. Such a short-term LT4 withdrawal also likely induced abnormal rCMRglu. Our study attempts to explain the possible mechanism of mood disorders related to transient hypothyroidism.